The Federal budget for the years 2019–2021: fiscal balance or economic growth? (conclusion on the draft Federal law No. 556362-7 “On the Federal budget for 2019 and the planning period 2020 and 2021”) - Solyannikova, S. P.; Alandarov, R. A.; Gorlova, O. S.; Karaev, A. K.; Makashina, O. V.; Masterov, A. I.; Ponkratov, V. V.; Sedova, M. L.; Tyurina, Yu. G.; Frumina, S. V. (Finansy: teoriâ i praktika (Online), 2018)
The authors present the results of the evaluation of the main provisions of the draft Federal budget regarding their compliance with the requirements of the budget legislation, and the documents of strategic planning of socio-economic development of Russia. At the same time, we concluded that the transition to a balanced budget and active accumulation of funds in the National Welfare Fund, along with a decrease in the dependence of the Federal budget on fluctuations in oil prices in world markets, will contribute to macroeconomic stability. However, the transition to a balanced budget is also due to the rejection of tax and budget incentives for the economy. We identified systemic problems and risks of the Federal budget for the medium and long-term. The authors also assessed the problems of implementation of the main provisions of the Decree of the President of the Russian Federation on May 7, 2018, No. 204 in the framework of the presented budget concept and budget policy.